Microstructural, mechanical, and optical characterization of an experimental aging-resistant zirconia-toughened alumina (ZTA) composite. Issue 12 (December 2020) - Lopes, A.C.O.; Coelho, P.G.; Witek, L.; Benalcázar Jalkh, E.B.; Gênova, L.A.; Monteiro, K.N.; Cesar, P.F.; Lisboa-Filho, P.N.; Bergamo, E.T.P; Ramalho, I.S.; Campos, T.M.B.; Bonfante, E.A.
Abstract: Objective: To evaluate the effect of aging on the microstructural, mechanical, and optical properties of an experimental zirconia-toughened alumina composite with 80%Al2 O3 and 20%ZrO2 (ZTA Zpex) compared to a translucent zirconia (Zpex) and Alumina. Methods: Disc-shaped specimens were obtained by uniaxial and isostatic pressing the synthesized powders (n = 70/material). After sintering and polishing, half of the specimens underwent aging (20 h, 134 °C, 2.2 bar). Crystalline content and microstructure were evaluated using X-ray diffraction and scanning electron microscopy, respectively. Specimens underwent biaxial flexural strength testing to determine the characteristic stress, Weibull modulus, and reliability. Translucency parameter (TP) and Contrast ratio (CR) were calculated to characterize optical properties. Results: ZTA Zpex demonstrated a compact surface with a uniform dispersion of zirconia particles within the alumina matrix, and typical alumina and zirconia crystalline content. ZTA Zpex and alumina exhibited higher CR and lower TP than Zpex. ZTA Zpex and Zpex showed significantly higher characteristic stress relative to alumina. While aging did not affect optical and mechanical properties of ZTA Zpex and alumina, Zpex demonstrated a significant increase in translucency, as well as a in characteristic stress. Alumina reliability was significantly lower than others at 300 MPa, ZTA Zpex and Zpex reliability decreased at 800 MPa, except for aged Zpex. Significance: While aging did not affect the mechanical nor the optical properties of ZTA Zpex and alumina, it did alter both properties of Zpex. The results encourage further investigations to engineer ZTA as a framework material for long span fixed dental prostheses specially where darkened substrates, such as titanium implant abutments or endodontically treated teeth, demand masking.